Association between lack of sexual interest and all-cause mortality in a Japanese general population: The Yamagata prospective observational study. - Kaori Sakurada; Tsuneo Konta; Narumi Murakami; Naoko Kosugi; Takafumi Saito; Masafumi Watanabe; Kenichi Ishizawa; Yoshiyuki Ueno; Takamasa Kayama (PLoS ONE, 2022)
Background Sexual interest is essential for maintaining positive sexual relationships and sexual function, which have recently been recognized as important indicators of good health and quality of life. Here, we prospectively investigated associations between sexual interest and mortality in a community-based population. Methods This study enrolled 20,969 subjects (8,558 males and 12,411 females) aged ≥ 40 years who participated in annual health check-ups in Yamagata Prefecture. Sexual interest was assessed by a self-report questionnaire. Associations between sexual interest and increased all-cause mortality, cardiovascular disease mortality, and cancer mortality were investigated by Cox proportional hazards modeling. Results During follow-up (median: 7.1 years), 503 subjects died; 67 deaths were due to cardiovascular disease, and 162 were due to cancer. Kaplan-Meier analysis showed that all-cause mortality and cancer mortality were significantly elevated among men who lacked sexual interest (log-rank P<0.0001, P<0.05). Cox proportional hazards model analysis with adjustment for age, hypertension, diabetes, dyslipidemia, smoking, alcohol drinking status, BMI, education, marital status, frequency of laughter, and psychological distress showed that the risk of all-cause mortality was significantly higher among men who lacked sexual interest than men who had sexual interest (hazard ratio [HR] 1.69; 95% confidence interval [CI], 1.17-2.44). Conclusion Lack of sexual interest is suggested to be a risk factor for all-cause mortality in Japanese males over 40 years old. This finding has implications for the importance of sexual interest in increasing longevity in this population.